2020
DOI: 10.1002/jia2.25505
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for the use of mathematical modelling to support decision‐making on integration of non‐communicable diseases into HIV care

Abstract: Introduction: Integrating services for non-communicable diseases (NCDs) into existing primary care platforms such as HIV programmes has been recommended as a way of strengthening health systems, reducing redundancies and leveraging existing systems to rapidly scale-up underdeveloped programmes. Mathematical modelling provides a powerful tool to address questions around priorities, optimization and implementation of such programmes. In this study, we examine the case for NCD-HIV integration, use Kenya as a case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…For tuberculosis and diabetes integration there were few studies in low-income countries (LICs) and limited literature in middle income countries (MICs)–only 56 across the search period. This suggests that countries with greater resources have been relatively more proactive to integrate care for these conditions, whereas early LIC developments would appear to have focused on HIV (for which many examples exist), due to greater disease prevalence, resources, and–crucially—donor support to foster integration [ 9 13 , 127 , 128 ]. The onset of COVID-19 produced a surge of integration of COVID-19 and cardiometabolic disease, and COVID-19 and diabetes or tuberculosis, comprising almost half of all studies reviewed.…”
Section: Discussionmentioning
confidence: 99%
“…For tuberculosis and diabetes integration there were few studies in low-income countries (LICs) and limited literature in middle income countries (MICs)–only 56 across the search period. This suggests that countries with greater resources have been relatively more proactive to integrate care for these conditions, whereas early LIC developments would appear to have focused on HIV (for which many examples exist), due to greater disease prevalence, resources, and–crucially—donor support to foster integration [ 9 13 , 127 , 128 ]. The onset of COVID-19 produced a surge of integration of COVID-19 and cardiometabolic disease, and COVID-19 and diabetes or tuberculosis, comprising almost half of all studies reviewed.…”
Section: Discussionmentioning
confidence: 99%
“…Subgroup analysis by publication year showed no significant difference between studies published between (2014 and 2019) and those published between (2020 and 2022). In areas where the prevalence of hypertension is higher among PLHIV, integrating hypertension services into routine HIV care by capitalizing the preexisting health system and following multidisciplinary approaches will be key [ 45 ]. It is also important to recognize that the trend in the prevalence of hypertension might vary over time in different countries as ART exposure, severity of the disease in PLHIV and access to healthcare service changes.…”
Section: Discussionmentioning
confidence: 99%
“…The design of additional studies will depend on evidence gaps identified. These can include mixed methods implementation studies to document quality, coverage, impact, and acceptability, qualitative explorations of user and health care worker experiences, time-motion studies to estimate health workforce need and to identify areas for increasing efficiencies, and costing and economic analyses, including mathematical models to assess cost-effectiveness or help in budget planning [ 33 34 ].…”
Section: Dsd For Hypertension: What Would It Take?mentioning
confidence: 99%